Faktor-Faktor Yang Mempengaruhi Produksi Dan Pendapatan Usahatani Jeruk Keprok Soe Di Kabupaten Timor Tengah Selatan - Chris Natali Namah (Partner, 2012)
Factors Affecting The Production and Revenue Of Keprok Soe Citrus Farming in Timor Tengah Selatan.Â  The aim of this study is to analyse the factors influence the production and income of the Keprok SoE Citrus farming. The location is purposively defined in North Mollo Subdistrict as a citrus production central. Two villages are choosen (Ajaobaki and Fatukoto) because they are the bigger producers of Keprok SoE Citrus farming. 50 farmers are choosen as the respondents. The data are collected by doing some interviews. Cobb-Douglass production function is employed to analyse the factors influencing the production and income. As the results of the production analysis, the age of the plants has impact to the production with negative sign, whereas labor, harvested area, use of fertilizer, experience of the farmers and dummy variables of education have impacts to the production with positive signs. The age of the farmers, price of the seeds, price of the Californian porridge, wage and dummy of education have negatively sign impacts to the farmersâ€™ income. Keywords: Keprok SoE Citrus farming, production, income.